2000
DOI: 10.1074/jbc.m005264200
|View full text |Cite
|
Sign up to set email alerts
|

RhoA Prenylation Is Required for Promotion of Cell Growth and Transformation and Cytoskeleton Organization but Not for Induction of Serum Response Element Transcription

Abstract: The importance of post-translational geranylgeranylation of the GTPase RhoA for its ability to induce cellular proliferation and malignant transformation is not well understood. In this manuscript we demonstrate that geranylgeranylation is required for the proper cellular localization of V14RhoA and for its ability to induce actin stress fiber and focal adhesion formation. Furthermore, V14RhoA geranylgeranylation was also required for suppressing p21 WAF transcription, promoting cell cycle progression and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 61 publications
6
71
0
2
Order By: Relevance
“…We observed no significant differences at the mRNA level between the set of genes expressed in either cell line (data not shown), suggesting that signaling by K-Ras is independent of the identity of the prenyl group. This is consistent with reports in which RhoA signaling was shown to be independent of the identity of the prenyl group (41,42). We conclude that K-Ras-F and K-Ras-GG are functionally equivalent and that the effect of FTIs on K-Ras-transformed cells probably results from inhibition of other farnesylated proteins.…”
Section: Design and Construction Of Mutant Ras Proteins-in Order Tosupporting
confidence: 81%
“…We observed no significant differences at the mRNA level between the set of genes expressed in either cell line (data not shown), suggesting that signaling by K-Ras is independent of the identity of the prenyl group. This is consistent with reports in which RhoA signaling was shown to be independent of the identity of the prenyl group (41,42). We conclude that K-Ras-F and K-Ras-GG are functionally equivalent and that the effect of FTIs on K-Ras-transformed cells probably results from inhibition of other farnesylated proteins.…”
Section: Design and Construction Of Mutant Ras Proteins-in Order Tosupporting
confidence: 81%
“…This allows separating extracts into an aqueous and detergent phase, and previous work showed that unprenylated Ras and Rho proteins partition into the aqueous phase, while prenylated proteins partition into the detergent phase [7,20]. In the absence of lovastatin, RhoA was largely in the detergent phase (Fig.…”
Section: Lovastatin Increases Expression Of Unprenylated Rhoa B Andmentioning
confidence: 99%
“…Prenylation of Rho proteins is essential for proper membrane localization, and appears to be required for most, but not all, known Rho functions [5][6][7][8]. HMG-CoA reductase (EC1.1.1.88) inhibitors (statins) reduce the synthesis of mevalonate, the precursor of cholesterol, and of farnesyl and geranyl-geranyl isoprenoids [9].…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence histology was done as described elsewhere (9). Cells were seeded on glass coverslips in six-well plates and were treated with either vehicle or erlotinib at 5 μmol/L for 48 hours.…”
Section: Fluorescencementioning
confidence: 99%